Effect of Primary Recrystallized Microstructure and Nitriding on Secondary Recrystallization in Grain Oriented Silicon Steel by Low Temperature Slab Reheating - LIU Gong-tao; LIU Zhi-qiao; YANG Ping; MAO Wei-min (Cailiao gongcheng, 2018)
Different primary recrystallized grain sizes were obtained by controlling decarburization process in grain oriented silicon steel produced by low temperature slab reheating technique. The effect of primary grain size on secondary recrystallization and magnetic properties was studied. The appropriate nitrogen content after nitriding was explored in case of very large primary grain size, and the effect of {411}〈148〉 primary recrystallized texture on the abnormal growth behavior was discussed. The results show that an increase in average primary grain size from 10μm to 15μm leads to an increase of secondary recrystallization temperature and a sharper Goss texture with higher magnetic permeability, in the condition of a very large average primary grain size of 28μm, the suitable amount of nitrogen increases to about 6×10-4. The {411}〈148〉 oriented grains in primary recrystallized microstructure can easily grow into larger sizes due to their size advantage, and thus hinder the abnormal growth of secondary grains, moreover, the hindering effect is more pronounced in the abnormal growth of Brass-oriented grains due to their misorientation with low migration rate other than Goss grains.